Sustainable Logistics: Decarbonizing Inbound Logistics Using Milk Run - Edhie Budi Setiawan; Djonatan Richard Setiyanto; Zaenal Abidin; Sita Aniisah Sholihah; Nashrullah Nashrullah; Primadi Candra Susanto; Rinaldi Rinaldi (Dinasti International Journal of Education Management and Social Science, 2026)
The modern transportation and logistics landscape is undergoing a dramatic transformation, driven by the relentless pursuit of efficiency, resilience, and sustainability. A critical aspect of modern green supply chain management is optimizing transportation routes to reduce fuel consumption and minimize carbon footprints. Building on this paradigm, this study examines the impact of the Milk Run Method on distance traveled, fuel consumption, and carbon footprint during delivery, comparing its implementation with the Point-to-Point delivery method. Milk Run method showed a 29% reduction in travel distance and 9% lower fuel usage and CO₂ emissions across six routes. Its effectiveness, however, depended on supplier proximity and cargo volume.